Mercury Intrusion Effects Modelled in Pores with Axial Symmetry and Attenuated Cross Section - Isaac Kornhauser; Carlos Felipe; Juan Marcos Esparza; Armando Domínguez; Fernando Rojas (Adsorption Science & Technology)
The study of Hg intrusion in axially symmetric pores modelled from a circular function, including a cross-sectional attenuation, unveils or ratifies some interesting effects. One of them is the influence of the pore-wall angle of inclination on the intrusion pressure and meniscus radius of curvature. Another one is that Hg penetration in pores of this sort cannot proceed gradually but only in a jump-like manner. Virtual penetration curves indicate Laplace stable or unstable states as well as the virulence of the irreversible penetration of pores with a varying cross section. It is also important to point out that, in structures depicting a sinuous cavity to throat inter-connections, a single meniscus can be transformed into more than one meniscus by a sort of snap-off mechanism. Hysteresis in these structures can be expected to be more intense as the pore entities become more sinuous. Finally, it is also important to mention that the onset of liquid penetration is not always occurring at the minimum cross section of a pore channel, but at a specific point beyond this occlusion.